Формування науково-практичних засад опису рукописних книг та стародруків у науковій діяльності В. М. Перетца в Україні - Міщук, С. (Національна бібліотека України ім.В.І.Вернадського, 2007)
This work highlights scientific input into development of scientific, bibliographical indexing of codexes and early printed books and scientific study techniques applied to texts of rare books by famous literary scholar V. M. Perets (1870–1935), and members of his Russian Philology Seminary O. Nazarevsky, O. Bagriy, M. Gudziy, S. Maslov, O. Gruzinsky, E. Tymchenko, S. Scheglova and V. Adrianova, and others who worked under his supervision at the Imperial University of St. Vladimir during 1919–1917. Activity of Seminary in respect to some Ukrainian institutions that kept rare and valuable collections of books and manuscripts in Kyiv, Nizhin, Poltava, Zhitomir, Katerynoslav, Lviv is also reviewed.